Konflik Pekerjaan‐Keluarga dengan Kepuasan Kerja: Metaanalisis - Triana N. E. D. Soeharto (Faculty of Psychology, Universitas Gadjah Mada, 2009)
This review examined the relationship between work‐family conflict and job satisfaction. The quantitative review involved 7 studies from 11 articles.The metaanalysis results showed that work‐family conflict has a correlation on job satisfaction. Result indicated that work‐family conflict influence people`s feelings and attitudes about jobs. Future research should strive for examination of how sample influences findings.